Differenciált Fejlesztés Heterogén Tanulócsoportban - K. Nagy Emese (2020)
The Complex Basic Program (CBP) is an Educational Program, based on professional teacher development. The aim of the paper is to show the Differentiated Development in Heterogeneous Learning Groups (DDHLG) program, which is the essential element of Complex Basic Program. In this paper we learn about the Differentiated Development in Heterogeneous Learning Groups, which is a teaching program that aims to create more equitable classroom atmosphere in which status differences among pupils do not play a significant role and don’t hinder their learning efforts. It also radically changes the teaching perspective - it allow s for appreciation and evaluation of a variety of intelligence forms and capacities and it makes children active actors o f their own learning. This pedagogical practice is thus successful in introducing high quality education to diverse classrooms, in which social backgrounds and intellectual capacities of pupils differ substantially. It encourages the personal involvement of students in the learning-teaching process, focusing on student collaboration. We also show the importance of the Differentiated Development in Heterogeneous Learning Groups program, namely: - why there is a need for knowledge development and apprenticeships for teacher training, - why equitable and strong scientific results are crucial to the experience of both teachers and students.